P863 Exploring patients' perceptions of clinical research in inflammatory bowel disease and barriers to participating in clinical trials. (30th January 2023) - Chatten, K; Kalra, P; Bower, P; Mclaughlin, J; Ghosh, S; Limdi, J
Abstract: Background: The rising incidence and prevalence of inflammatory bowel disease (IBD), its uncertain aetiology and multidimensional and negative effects on people's lives have underscored the importance and need for research across disciplines. Despite this, participation in research in IBD remains relatively low, with virtually no data exploring patients' perceptions and barriers to participation in research among people living with IBD. This is a preliminary report from an on-going study in the UK. Methods: Consecutive outpatients attending IBD clinics at our centre were invited to complete a questionnaire survey. Information on patient demographics, disease duration and activity were recorded and patient perceptions and barriers to participating in research were explored. Results: Of 401 patients approached to date, 332 (82.8%) consented to complete the questionnaire. Of 60 patients who declined, 70% were male. Among 332 participants, 176 (53.2%) were female, age between 18- 80. 164 participants had Crohn's disease (CD, 49.4%), 147 ulcerative colitis (UC) (44.3%), 8 (2.4%) had IBD-unspecified and 13 (3.9%) were unsure of their diagnosis. 209 (63%) patients were on biologics. The mean Harvey Bradshaw Index (HBI) was 4.4 (CD) and partial Mayo score 2.1 (UC). 303 (91.3%) participants said they would participate in research, but only 65.3% stated they would be interested in drug trials. Reasons cited for participation were to advance medical knowledge (277/303, 91.4%) followed by the possibility of "effective" treatment (231/303, 76.2%). Of those that stated they were not interested in research at all, 17/29 (58.6%) were male. Their most important reasons for not wanting to participate were time constraints followed by concern for health. Although optional to answer if interested in research, a further 100/303 (33%) cited concern for own health (54/100, 54.0%) followed by time constraints (34/100, 34%) as barriers. Only 15 felt deterred by the possibility of receiving a placebo (15/100, 15%) or having more tests (12/100 12%). Direct conversation with their doctor (201/332, 60.5%) was felt most motivational to participation in research. Conclusion: Most patients express interest in participating in IBD research, with majority interested in participating drug trials. The placebo element did not deter sentiment about participation in trials and direct communication with clinicians is valued. More data will be available for analysis and reporting in the coming months.